Social Capital And Food Security Of Poor Households In Watersheds During The Covid-19 Pandemic - Meyzi Heriyanto; Khairul Anwar; Ismandianto; Ruzikna; Mashur Fadli; Yusmar Yusuf (International Journal of Educational Research & Social Sciences, 2021)
Poor Household Research on Social Capital and Food Resilience (RTM) The socioeconomic imbalances of impoverished households in the Siak watershed areaprovide the backdrop for the execution of the 2020 Social Distancing and PSBBpolicies. The condition of the population in the Tanjung Rhu and Rumbai PesisirSub-Districts that has tested positive for Covid-19 is relatively low, but the potentialfor the rise and socio-economic gaps is substantial. This research sought to answerthe following key question: How can social capital be mobilized to increase foodsecurity for poor households in the context of social distancing and PSBB policies intwo Pekanbaru sub-districts? Social participation and social capital theory canprovide answers to this topic. The goal of this study was to look at the state of socialcapital and the possibilities for enhancing food security for disadvantaged familiesin the two Covid-19 in the year 2020: (1) The level of public trust in workingtogether to strengthen food security during the implementation of social distancingand PSBB policies; (2) The level of a family trust in working together to strengthenfood security during the implementation of social distancing and PSBB policies; (3)The benefits of formal and informal social networks in dealing with SocialDistancing and PSBB; (4) The benefits of socialization medium for formalgovernment and informal regulations fo? The following are the findings of theresearch given in this paper: To begin with, this PSBB policy influenced the riverflow resilience of impoverished households in Pekanbaru City's Tanjung Rhu andMeranti Pandak villages. Second, the components of social capital that weresignificantly related to community and household trust in establishing relationshipswithout mutual suspicion, household trust in being able to maintain a sustainableenvironment, and in dealing with the impact of the implementation of Covid 19 afterthe PSBB's enactment. Third, social capital can be established and improved at thecommunity level in the form of social institutions that help improve food security inpoor communities.